Macroeconomic Experiences of the Transition Economies in Indochina - Pham, Chi (IMF Working Papers; Working Paper, 1996)
This paper examines stabilization policies in Vietnam, Cambodia, and Laos since the late 1980s. Compared with other transition economies, the Indochinese countries avoided an output collapse and moved quickly to strong GDP growth and low inflation. Each adopted a similar mix of policies centered on flexible exchange rates, high real interest rates, fiscal adjustment through expenditure cuts, and the imposition of hard budget constraints on public enterprises. In none of the countries was an exchange rate anchor considered feasible, and money-based stabilization proved effective, despite evident instability in the demand for money.